The Influence Of Price Perception And Service Quality On Consumer Satisfaction (Survey on Consumer Alfa Studios at Tasikmalaya City) - Gilang Dayu Pangestu; Ari Arisman; Suci Putri Lestari (Journal of Indonesian Management, 2023)
This purpose of this study to determine the influence of price perception and service quality on consumer satisfaction (Survey on Consumer Alfa Studios at Tasikmalaya City). The method used is a quantitative method with a research sample of 100 respondents who are a consumer Alfa Studios at Tasikmalaya City. The data is used primary data and secondary data. The analitytical tool in this research is multiple regression using by SPSS version 25. The result showed that simultaneously price perception and service quality has a significant influence on consumer satisfaction. Partially price perception has positive and significant influence on consumer satisfaction. Partially service quality has positive and significant on consumer satisfaction.